Neuroimaging evidence for sensitivity to orthography-to-phonology conversion in native readers and foreign learners of Chinese - Yu, Anya; Chen, Makayla S. Y.; Cherodath, Sarika; Hung, Daisy L.; Tzeng, Ovid J. L.; Wu, Denise H. (My University, 2019)
Through recent neuroimaging research into brain mechanisms of proficient reading and literacy acquisition in different languages, a common neural network supporting reading has been identified in native readers across various writing systems. However, whether the same or different brain regions are involved in learning to read a foreign language is largely unexplored. To investigate (1) neural correlates of literacy acquisition of Chinese in adults whose learning of this logographic language was relatively late, and (2) to examine which cognitive factors might be predictors of literacy acquisition that would modulate the computation demands on reading-related brain regions, native and non-native Chinese readers were recruited to participate in pronunciation and color verification tasks using Chinese pseudo-phonograms in fMRI while their sensitivity to extracting systematic regularity in nonverbal materials, as well as their IQ and working memory, was measured in a visual statistical learning (VSL) task. The results indicated that native participants activated a left lateralized reading network that is consistent with previous research on orthography-to-phonology conversion (OPC) of Chinese, while a similar but extensive network that also includes regions in the right hemisphere was engaged in the non-natives. Within this network, left inferior frontal sites were found to be crucial to the mapping of Chinese pseudo characters to potential sounds especially in non-natives. More important, only the VSL scores of native and non-native participants, but not their general cognitive abilities, were negatively correlated with the brain activities in the left inferior parietal and left inferior frontal regions, respectively, suggesting that the fundamental capacity of SL supports literacy acquisition through modulating computation demands on the brain regions associated with OPC processing, which is critical to Chinese character recognition.
Keywords: Statistical learning; Foreign literacy acquisition; Bilingualism; Orthography-to-phonology conversion; fMRI